ANALISIS YURIDIS TERHADAP PEMUTUSAN HUBUNGAN KERJA MASSAL PADA PT GOTO GOJEK TOKOPEDIA TBK DALAM PRESPEKTIF UNDANG-UNDANG KETENAGAKERJAAN - Achmad Fahri (PT. Saha Kreasi Indonesia, 2026)
Mass layoffs in the digital industry have become an increasingly prevalent phenomenon in line with global economic dynamics and corporate efficiency demands. This study aims to conduct a juridical analysis of mass termination of employment carried out by PT GoTo Gojek Tokopedia Tbk from the perspective of Indonesian labor law. The research employs a normative juridical approach with a case study method. Data are collected through library research, including statutory regulations, academic literature, and relevant media sources. The findings indicate that mass layoffs may be legally justified when based on legitimate grounds, such as corporate efficiency, and conducted in accordance with procedures stipulated in Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan as amended by Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja. Furthermore, employers are required to fulfill workers’ rights, including severance pay and other compensations as regulated by law. However, in practice, discrepancies remain between legal norms and their implementation, particularly concerning transparency and substantive justice for workers. This study concludes that although mass layoffs are normatively permissible, stronger labor protection is necessary to ensure a balance between corporate interests and workers’ rights.